2013
DOI: 10.1007/s10653-013-9576-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of water pollution as a consequence of a leachate plume migration from a municipal landfill site (Tucumán, Argentina)

Abstract: Landfills constitute potential sources of different pollutants that could generate human health and environmental problems. While some landfills currently work under the protection of a bottom liner with leachate collection, it was demonstrated that migration could take place even yet with these cautions. The purpose of this paper is to assess the pollution caused by a leachate plume from a municipal landfill that is affecting both groundwater and surface waters. The research was carried out at Pacará Pintado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Similar values of Cd were reported [33,34]. The values were higher than the reported work [29] and lower than obtained work [25,52].…”
Section: Potentially Toxic Elements Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…Similar values of Cd were reported [33,34]. The values were higher than the reported work [29] and lower than obtained work [25,52].…”
Section: Potentially Toxic Elements Analysessupporting
confidence: 89%
“…The upstream sample value in the wet season was the only Mn value equal to the WHO threshold, while the rest were within the limit. The values from this study were higher than the obtained value [32] and were lower than the values [52].…”
Section: Potentially Toxic Elements Analysescontrasting
confidence: 86%
“…showed almost same results by observing considerable amount of TDS, EC, NO 3 − and PO 4 − 3 in the ground water samples taken from near the land ll site thus concluding that ground water quality is signi cantly affected by leachate percolation. Similarly, Fernández et al (2014) observed the impacts of leachate plume up to 900 m from the land ll site. As the leachate reaches the saturated zone, it forms plume which spreads in the direction of ow of water and contaminates the ground water (Vasanthi et al, 2008).…”
Section: Physicochemical Parametersmentioning
confidence: 87%
“…Landfill is a place for various kinds of waste so that leachate contains various types of pollutants that have the potential to disturb the environment and human health. Leachate can seep into the ground, or flow on the ground surface and lead to river water flow [5,6,7,8,9]. Each landfill has different leachate characteristics depending on the processes that occur in the landfill, which include physical, chemical and biological processes [10].…”
Section: Introductionmentioning
confidence: 99%